2016
DOI: 10.1088/1475-7516/2016/03/062
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the NVSS number count dipole

Abstract: We present a realistic modeling of the dipole component of the projected sky distribution of NVSS radio galaxies. The modeling relies on mock catalogs generated within the context of ΛCDM cosmology, in the linear regime of structure formation. After removing the contribution from the solar motion, the mocks show that the remaining observed signal is mostly (70%) due to structures within z 0.1. The amplitude of the model signal depends on the bias factor b of the NVSS mock galaxies. For sources with flux densit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
122
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(142 citation statements)
references
References 74 publications
18
122
2
Order By: Relevance
“…The shot noise for the same flux cut is 3.7×10 −5 , this gives an error estimate on dipole magnitude euqal to 0.003. Although this value of dipole is lower than the value 0.070 ± 0.004 obtained in (Bengaly et al 2018), however, it remain 3 to 5 times higher than the value obtained with NVSS for different flux cuts Tiwari & Nusser 2016). The results with mask 2, shown in the bottom panel of figure 3, also show very large C l values for low multipoles l < 10.…”
Section: L Estimationcontrasting
confidence: 51%
See 1 more Smart Citation
“…The shot noise for the same flux cut is 3.7×10 −5 , this gives an error estimate on dipole magnitude euqal to 0.003. Although this value of dipole is lower than the value 0.070 ± 0.004 obtained in (Bengaly et al 2018), however, it remain 3 to 5 times higher than the value obtained with NVSS for different flux cuts Tiwari & Nusser 2016). The results with mask 2, shown in the bottom panel of figure 3, also show very large C l values for low multipoles l < 10.…”
Section: L Estimationcontrasting
confidence: 51%
“…On the contrary the C l 's from NVSS as computed by ; Nusser & Tiwari (2015); Bengaly et al (2018); Dolfi et al (2019) are found to be roughly consistent with ΛCDM for l > 1. The dipole amplitude from NVSS is more than 2 sigma disagreement with ΛCDM predictions Tiwari & Nusser 2016) whereas the TGSS ADR1 dipole according to Bengaly et al (2018), is almost 5 times larger than the prediction. The Bengaly et al (2018) doubt this excess signal to be physical and say that their results may be due to systematics in data.…”
Section: L Estimationmentioning
confidence: 75%
“…E-mail: carlosap@on.br † E-mail: bernui@on.br ‡ E-mail: ivan@fis.unb.br § E-mail: alcaniz@on.br Bernui et al 2007;Abramo et al 2009;Akrami et al 2014;Bernui et al 2014;Ade et al 2015d;Schwarz et al 2016); ii) large velocity flows from analyses of kinematic Sunyaev-Zeldovich effect in GCs (Kashlinsky et al 2009(Kashlinsky et al , 2011Atrio-Barandela et al 2015), although some controversy have been pointed out by Osborne et al (2011), regarding the validity of these results 1 ; iii) large number counts dipole anisotropy found in high-z radio sky (Blake & Wall 2002;Singal 2011;Rubart & Schwarz 2013;Fernández-Cobos et al 2014;Tiwari et al 2015;Tiwari & Nusser 2016). All these results pose a potential challenge for the concordance model of Cosmology, which relies upon the large-scale isotropy assumption.…”
mentioning
confidence: 99%
“…At the same time, observations of the largely isotropic Hubble expansion and CMB suggest that we are relatively close to the center. This could explain small yet statistically significant (∼ 3σ) anisotropies detected in both the distribution of radio galaxies (Singal 2011;Tiwari and Nusser 2016) and the CMB (Bennett et al 2011;Ade et al 2014), which challenge the isotropy assumption of the ΛCDM model. Note that all anisotropies are expected to disappear when viewed from the exact center of the star.…”
Section: Discussionmentioning
confidence: 99%